2022
DOI: 10.18388/abp.2020_5771
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin accessibility landscape in the dental pulp of mouse molars and incisors

Abstract: The dental pulp is a promising source of progenitor cells for regenerative medicine. The natural function of dental pulp is to produce odontoblasts to generate reparative dentin. Stem cells within the pulp tissue originate from the migrating neural crest cells and possess mesenchymal stem cell properties with the ability to differentiate into multiple lineages. To elucidate the transcriptional control mechanisms underlying cell fate determination, we compared the transcriptome and chromatin accessibility in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…3 Stem Cells International genomic states. Previously, using ATAC-seq and hmeDIPseq assays, we identified accessible chromatin regions and genome-wide enrichment of 5hmC in the mouse dental pulp [30,31]. By analyzing these datasets, we found that the vast majority of genes encoding protein partners and downstream targets of KMT2D and KDM6A exhibit open chromatin enriched in 5hmC (data not shown).…”
Section: 3mentioning
confidence: 90%
“…3 Stem Cells International genomic states. Previously, using ATAC-seq and hmeDIPseq assays, we identified accessible chromatin regions and genome-wide enrichment of 5hmC in the mouse dental pulp [30,31]. By analyzing these datasets, we found that the vast majority of genes encoding protein partners and downstream targets of KMT2D and KDM6A exhibit open chromatin enriched in 5hmC (data not shown).…”
Section: 3mentioning
confidence: 90%